Teachers' digital competence in utilizing educational software in accounting, business, and management strand - Vedelyn Bituin Dorado; Ruth Alvar Ortega-Dela Cruz (Universidade Estadual de Maringá, 2024)
Technological breakthroughs have caused significant changes in the field of accounting, business, and management (ABM); thus, demand congruence with teacher's technology skills in handling ABM courses. This study used the descriptive-survey method of research using questionnaire as the main research tool in gathering data. The researcher utilized the combination of quantitative and qualitative research methods. The former was used to describe the characteristics of ABM teachers in terms of their socio-demographic profile and to discuss and assess their digital competence while the latter was applied to examine the strengths and weaknesses of the ABM educational software. A total of 138 ABM teachers participated in the study. Findings reveal that the level of teachers' digital competence is mostly high. Specifically, they are very much capable in using educational software that are needed in their everyday work but not on software needed to assist them in the teaching-learning process.  Thus, this study has implications not only for ABM teachers who play a significant role in equipping the future workforce in the field of ABM. This study calls for continuous support from the Philippine Department of Education. This sector is responsible for providing trainings and assistance to teachers' digital competencies particularly in the utilization and proper integration of educational software to the various ABM subjects. Together with school leaders and administrators, they must provide opportunities for the teachers to receive hands-on trainings where tool kits and manuals will be provided.  Such ongoing initiatives will lead to better and quality education where learners are equipped to dive into the digital world of ABM.